Late-instar larva of Scydmaenus (Parallomicrus) rufus Müller & Kunze (Coleoptera: Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2015)
The late-instar (most likely the last instar) larva of Scydmaenus (Parallomicrus) rufus is described. A comparative study with other known larvae of Scydmaenus (belonging to Scydmaenus s. str. and the subgenus Cholerus) is carried out and it is concluded that while the general body form and some characters are shared by immature Parallomicrus and Cholerus, there are nevertheless features present in Parallomicrus and Scydmaenus s. str. that are absent in Cholerus. A subcylindrical and strongly elongated body differentiates immature Parallomicrus from Scydmaenus s. str., while the following characters, present in Parallomicrus, are not known in Cholerus: a pair of long lateral setae on head capsule, four (and not five) pairs of dorsoanterior setae on the nasale, more than 10 teeth on the anteroventral margin of nasale instead of five only, three (and not two) solenidia on the antennomere III, three (and not two) pairs of labial setae, slightly (and not strongly) elongate abdominal segment IX, and abdominal segment X not constricted near base.